Ambivalensi Efektivitas Hukum Kekerasan Seksual Transnasional di Institusi Keagamaan melalui Red Notice Interpol: Studi Kasus Kekerasan Seksual Syekh Ahmad Al Misry (SAM) - Aorta Abdillah Alaa; Lu'Lu Salamah; Al Hafidh Muhammad Sobri; Miftahus Sholehudin (Fakultas Syariah dan Hukum Universitas Islam Negeri Sumatera Utara, 2026)
This article examines the ambivalence of legal effectiveness in addressing alleged transnational sexual violence involving Syekh Ahmad Al Misry (SAM) through the INTERPOL Red Notice mechanism. The central problem lies in the gap between the availability of domestic legal instruments and the practical limitations of law enforcement when the alleged perpetrator is located outside Indonesian jurisdiction, while victims remain exposed to religious power relations, stigma, a culture of silence, and the risk of suppression. This study aims to analyze how the law operates at the procedural level and to assess the limitations of its substantive effectiveness in ensuring victim protection and facilitating cross-border legal cooperation. It employs normative legal research informed by a socio-legal perspective and a qualitative single-case study design. The data were drawn from legislation, institutional documents, academic literature, and publicly accessible factual information, verified through source triangulation and analyzed using Soerjono Soekanto’s five factors of legal effectiveness. The findings indicate that reporting, investigation, victim protection, suspect designation, and the submission of a Red Notice demonstrate that the law has formally been activated. Its effectiveness nevertheless remains ambivalent because a Red Notice does not constitute an automatic international arrest warrant, the enforcement capacity of domestic law depends on the response of foreign authorities, and victim protection continues to be shaped by social structures and institutional culture. The study concludes that legal effectiveness in such cases should be assessed by the system’s capacity to ensure victims’ safety and recovery, establish institutional accountability, and achieve concrete cross-border legal coordination. Artikel ini mengkaji ambivalensi efektivitas hukum dalam penanganan dugaan kekerasan seksual transnasional yang melibatkan Syekh Ahmad Al Misry (SAM) melalui mekanisme Red Notice Interpol. Persoalan utama penelitian terletak pada kesenjangan antara tersedianya instrumen hukum nasional dan keterbatasan penegakannya ketika terduga pelaku berada di luar yurisdiksi Indonesia, sementara korban menghadapi relasi kuasa keagamaan, stigma, budaya diam, dan risiko pembungkaman. Penelitian ini bertujuan menganalisis cara hukum bekerja secara prosedural sekaligus menilai batas efektivitas substantifnya dalam perlindungan korban dan kerja sama lintas negara. Metode yang digunakan adalah penelitian hukum normatif dengan perspektif sosio-legal dan desain studi kasus tunggal yang dianalisis secara kualitatif. Data diperoleh dari peraturan perundang-undangan, dokumen kelembagaan, literatur akademik, serta data faktual terbuka yang diverifikasi melalui triangulasi sumber, kemudian dianalisis menggunakan lima faktor efektivitas hukum Soerjono Soekanto. Hasil penelitian menunjukkan bahwa proses pelaporan, penyidikan, perlindungan korban, penetapan tersangka, dan pengajuan Red Notice membuktikan hukum telah bergerak secara formal. Namun, efektivitasnya tetap ambivalen karena Red Notice bukan perintah penangkapan otomatis, daya paksa hukum nasional bergantung pada respons negara lain, dan perlindungan korban masih dipengaruhi struktur sosial serta budaya institusional. Penelitian ini menyimpulkan bahwa efektivitas hukum dalam perkara semacam ini harus diukur dari kemampuan sistem menjamin keamanan dan pemulihan korban, membangun akuntabilitas kelembagaan, serta mewujudkan koordinasi hukum lintas negara yang konkret.